PENGEMBANGAN PEDOMAN DAN ACUAN KURIKULUM PENDIDIKAN ANAK USIA DINI (PAUD) KURIKULUM KELOMPOK BERMAIN - W. P. Napitupulu (Perspektif Ilmu Pendidikan, 2007)
Any curriculum for any level of educational program should be based upon national standards. It is in order to educate students to be good citizens as it is for early childhood education. Besides, the development of a curriculum should pay attention to political ideology, philosophy of knowledge, social context and learning models as well. So, will the curriculum of playgroup apply those aspects. In particular, it should also emphasize psychological aspects or stages of a child development. Criteria for a curriculum development are content, process, competencies, quality of teachers, and resources for learning.